The COVID-19 Pandemic as a Challenge for Post-Soviet Central Asia Countries - A. M. Akhunov (Международная аналитика, 2020)
The coronavirus pandemic has a significant impact on socio-economic and political processes in Central Asia. The political specifics of the countries in the region affected the methods and approaches taken by the authorities of Kazakhstan, the Kyrgyz Republic, Uzbekistan, Tajikistan, and Turkmenistan to prevent the spread of infection. The article compares these approaches: from declaring a state of emergency and ordering a curfew to suppressing information about the spread of the epidemic. The impact of the pandemic on the relations of the Central Asian countries with Russia and the prospects for the development of Eurasian integration projects is also considered.